The Multifaceted Protective Role of Nuclear Factor Erythroid 2-Related Factor 2 in Osteoarthritis: Regulation of Oxidative Stress and Inflammation - Sheng W; Yue Y; Qi T; Qin H; Liu P; Wang D; Zeng H; Yu F (Dove Medical Press, 2024)
Weibei Sheng,1 Yaohang Yue,1 Tiantian Qi,1 Haotian Qin,1 Peng Liu,1 Deli Wang,1 Hui Zeng,2 Fei Yu1 1Department of Bone & Joint Surgery, National & Local Joint Engineering Research Center of Orthopaedic Biomaterials, Shenzhen Key Laboratory of Orthopaedic Diseases and Biomaterials Research, Peking University Shenzhen Hospital, Shenzhen, 518036, People's Republic of China; 2Shenzhen Second People's Hospital, The First Affiliated Hospital of Shenzhen University, Shenzhen, 518035, People's Republic of ChinaCorrespondence: Hui Zeng; Fei Yu, Email zenghui_36@163.com; oscarfyu@163.comAbstract: Osteoarthritis (OA) is a chronic degenerative joint disease characterized by the degradation of joint cartilage, subchondral bone sclerosis, synovitis, and structural changes in the joint. Recent research has highlighted the role of various genes in the pathogenesis and progression of OA, with nuclear factor erythroid 2-related factor 2 (NRF2) emerging as a critical player. NRF2, a vital transcription factor, plays a key role in regulating the OA microenvironment and slowing the disease's progression. It modulates the expression of several antioxidant enzymes, such as Heme oxygenase-1 (HO-1) and NAD(P)H oxidoreductase 1 (NQO1), among others, which help reduce oxidative stress. Furthermore, NRF2 inhibits the nuclear factor kappa-B (NF-κB) signaling pathway, thereby decreasing inflammation, joint pain, and the breakdown of cartilage extracellular matrix, while also mitigating cell aging and death. This review discusses NRF2's impact on oxidative stress, inflammation, cell aging, and various cell death modes (such as apoptosis, necroptosis, and ferroptosis) in OA-affected chondrocytes. The role of NRF2 in OA macrophages, and synovial fibroblasts was also discussed. It also covers NRF2's role in preserving the cartilage extracellular matrix and alleviating joint pain. The purpose of this review is to provide a comprehensive understanding of NRF2's protective mechanisms in OA, highlighting its potential as a therapeutic target and underscoring its significance in the development of novel treatment strategies for OA.Keywords: nuclear factor erythroid 2-related factor 2, osteoarthritis, chondrocytes, inflammation, oxidative stress